Texto como escritura: conselhos em alfabetização - Pacheco, Alice Virgínia de Oliveira (My University, 2022)
This dissertation critically analyzes the idea of text used for teaching literacy to students in the first year of Elementary School, investigating the text's scholastic functions and social and writing practices according to legislation regarding education. Through this analysis, the following research aims to motivate its reader to reflect upon the type of text used in the classroom with children who are developing literacy skills. The methodology used for this research is based on the childhood memories of a literacy teacher who was raised by her grandfather, who could not read nor write. He helped guide this research by inspiring this literacy teacher/researcher to create three guidances, being: I) locate in legislation and didactic material the idea of text for its scholastic function; II) locate in legislation and didactic material the idea of text as a social practice; III) locate the idea of the text created by writing. The third guidance proposes an expansion of the possibilities of a text which is done by reading through writing and writing through reading, those practices being intersected by life experiences. This study consists of theories by multiple renowned authors in the area of Pedagogy, including Maria do Rosário Longo Mortatti, and features the ideas of French author Roland Barthes as an introduction to the section about literacy. [resumo fornecido pelo autor]
Esta dissertação problematiza a noção de texto no ensino da alfabetização no 1° ano do Ensino Fundamental, investigando, por meio de legislações voltadas à educação, o texto para: a função escolar, prática social e escritura. Com isso, esta pesquisa tem o objetivo geral de problematizar a noção de texto no ensino da alfabetização no 1° ano do Ensino Fundamental. Assim, a investigação se constitui por um ensaio teórico com alguns autores clássicos da alfabetização e algumas legislações. O ensaio do texto dissertativo ocorre por meio das lembranças de infância desta professora-alfabetizadora-pesquisadora, criada por um avô que não sabia ler, nem escrever. A escrita passa a ser guiada por ele, numa voz que a dissertação assume e se transforma em três conselhos, a saber: I: Localize nas leis e em materiais didáticos a noção de texto para a função escolar; ll: Localize nas leis e em materiais didáticos a noção de texto como prática social; lll: Localize a noção de texto por escritura, que traz uma contribuição a sala de aula em alfabetização. Este último pretende alargar as possibilidades de um texto que se faz com a leitura pela escrita e a escrita pela leitura em meio à vida. [resumo fornecido pelo autor]
Keywords: Alfabetização; Textos; Escrituras; Letramento; Material didático; Literacy; Texts; Deeds; Literacy; Courseware